2014
DOI: 10.1118/1.4862514
|View full text |Cite
|
Sign up to set email alerts
|

A matter of collection and detection for intraoperative and noninvasive near‐infrared fluorescence molecular imaging: To see or not to see?

Abstract: Camera imaging performance could impact the success of future "first-in-humans" near-infrared fluorescence imaging agent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 29 publications
4
79
0
Order By: Relevance
“…An alternative proposed method for signal removal of background ambient light is to modulate the beam at high frequency and sample the signal with this same demodulation. This process pioneered by Zhu et al [21,22] allows fast capture although it can suffer from dynamic range limitations if the room lights are a major contributor to the overall detected intensity. The use of short (sub-millisecond) gate widths and room light based triggering allows images to be acquired during background light minimums which is beneficial in the context of dynamic range limitations.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative proposed method for signal removal of background ambient light is to modulate the beam at high frequency and sample the signal with this same demodulation. This process pioneered by Zhu et al [21,22] allows fast capture although it can suffer from dynamic range limitations if the room lights are a major contributor to the overall detected intensity. The use of short (sub-millisecond) gate widths and room light based triggering allows images to be acquired during background light minimums which is beneficial in the context of dynamic range limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies that employ NIRF imaging with ICG focus on pre-surgical and intraoperative sentinel LNM (SLNM) and dissection (31)(32)(33). While investigational camera designs have widely varying sensitivity (34,35), non-invasive NIRF imaging can detect the lymphatic vasculature located as deep as 3-4 cm beneath the tissue surface with as little as 10 μg of ICG in 0.1 ml in humans (36) using intensified camera technologies, and up to 5 μg of ICG in 10 μl in mice using electron multiplier CCD technology (37)(38)(39). In clinical studies, NIRF imaging using ICG has been demonstrated to detect subclinical lymphedema (40,41) to guide and assess lymphatico-venous anastomosis microsurgery in a case of lower extremity lymphedema (42), and has been found to be superior to lymphoscintigraphy in the diagnosis of lymphedema (43).…”
Section: Imaging Lymphatic Architecture In Humans and Micementioning
confidence: 99%
“…Liquid phantoms containing proteins and organic dyes are unsatisfactory working standards, since they typically are single use, often unstable, and are not robustly reproducible. Previously, we developed stable, far red and near-infrared fluorescent solid working standards for characterizing the sensitive collection and detection of fluorescence emanating from a multiply scattering medium in order to compare fluorescence imaging devices [6]. Specifically we embedded QDots 800 (Q21771MP, Invitrogen, Carlsbad, CA) in increasing pM -nM concentrations with TiO 2 , and polyethylene in the wells of a 96 well assay plate to create stable, fluorescent working standards that emitted dim fluorescence >720 nm when excited with 690 nm excitation light for assessment of fluorescent contrast and SNR as previously described [6].…”
Section: Camera Performance Assessment Using Solid Working Standardsmentioning
confidence: 99%
“…Previously, we developed stable, far red and near-infrared fluorescent solid working standards for characterizing the sensitive collection and detection of fluorescence emanating from a multiply scattering medium in order to compare fluorescence imaging devices [6]. Specifically we embedded QDots 800 (Q21771MP, Invitrogen, Carlsbad, CA) in increasing pM -nM concentrations with TiO 2 , and polyethylene in the wells of a 96 well assay plate to create stable, fluorescent working standards that emitted dim fluorescence >720 nm when excited with 690 nm excitation light for assessment of fluorescent contrast and SNR as previously described [6]. Contrast was computed from the ratio of the 720 nm fluorescent signal averaged across wells with and without QDots 800 while SNR was computed from their difference in fluorescent intensity divided by the standard deviation of the intensities from the well without QDots 800.…”
Section: Camera Performance Assessment Using Solid Working Standardsmentioning
confidence: 99%
See 1 more Smart Citation